تاثير برامج الدراما الكورية عبر منصة نتفليكس على الثقافة الجزائرية - راشة بن ساجة; فاطمة الزهراء مصيطفي; د/ عطالله طريف (جامعة عمار ثليجي الاغواط, 2024)
الملخص : تسعى هذه الدراسة للتعرف على تأثير برامج الدراما الكورية عبر منصة نتفليكس على الثقافة الجزائرية حيث هدفت الدراسة الكشف عن تقيم المشاهدات الجزائريات الثقافية الكورية من خلال برامج الدراما عبر نتفلكس ، والتعرف على مظاهر الثقافة الكورية على المشاهدات الجزائريات ومعرفة أثرت برامج الدراما الكورية عبر منصة نتلفكس على الثقافة الجزائرية، ولتحقيق لذلك استخدمنا المنهج العلمي كما وظفنا استمارة الإستبيان التي تم توزيعها بشكل إلكتروني، حيث توجينا إلى مبحوثين الدراسة وهم المشاهدات الجزائريات من كل الأصناف العمرية للدراما الكورية عبر منصة نتفليكس ، وتوصلت الدراسة الى النتائج التالية :الدراما الكورية تجذب الجزائريات من مختلف الأعمال والخلفيات الاجتماعية وتحظى الدراما بشعبية واسعة في جميع أنحاء البلاد، قد يكون للدراما الكورية تأثيرا قويا وجذابا على الجمهور الجزائري بشكل عام والمشاهدات الجزائريات بشكل . -الجزائريات يستمتعن بمشاهدة الدراما الكورية بشكل متسلسل وفردي ويعبرن عن اراءهن وتجاربهن من خلال وسائل التواصل الاجتماعي هذه العادات تعكس رغبتهن اهتمامهن بالتفاصيل والتعاطف مع الشخصيات والقصص، بالإضافة الى رغبتهن في التواصل مع المجتمع المشترك في مشاهدة الدراما الكورية . -المشاهدات الجزائريات يشاهدن الدراما الكورية عبر منصة نتفلكس بسبب التمثيل العالي الجودة ورغبتهن في تعلم اللغة الكورية والدافع الرئيسي انتشار ثقافة الماليو عبر السنوات التالية بشكل دارج وكل هذه الأسباب والدوافع تشير الى تنوع اهتمامات المشاهدات واستمتاعهن بمشاهدة الدراما الكورية تحت غرض التسلية والترفيه . -هناك اختلاف في الآراء حول المظاهر التي تبتنيها منصة نتفلكس من الثقافة الكورية حيث يمكن أن تكون هناك وجهات نظر سلبية تركز على الاحتكار ، واخرى ايجابية تركز على التعريف بثقافة كوريا الجنوبية وتشجع التبادل الثقافي . -هناك تأثيرا فعليا لمنصة نتفلكس على الثقافة الجزائرية وانعكاسها على المشاهدات الجزائريات هذا الانعكاس يعكس تبنيهم لبض جوانب الثقافة الكورية وقبولها في حياتهن اليومية، الا هذا التأثير لا ينعكس كليا على الثقافة الجزائرية بل هو محدود لمظاهر معينة مثل الفن والجمال والأزياء والاكلات وتعلم اللغة . -منصةNeflix تستثمر 2.5 مليار دولار في انتاج المحتوى الكوري وتقديمه بأجود التقنيات الا أنها تتعمد ادخال بعض المحتوى الذي يسني للعرب انكار دخلية على المجتمع الجزائري والعربي بصفة عامة. الكلمات المفتاحية : الدراما الكورية، منصة نتفليكس ، الثقافة الجزائرية . Summary : This study seeks to identify the impact of Korean drama programs via the Netflix platform on Algerian culture. The study aimed to reveal the evaluation of Algerian women’s cultural Korean viewers through drama programs via Netflix, to identify aspects of Korean culture on Algerian women viewers, and to know the impact of Korean drama programs via the Netflix platform on culture. To achieve this, we used the scientific method and employed a questionnaire form that was distributed electronically, where we addressed the study subjects, namely Algerian female viewers of all age groups of Korean drama via the Netflix platform, and the study reached the following results: Korean drama attracts Algerian women from different professions and social backgrounds, and the drama is widely popular throughout the country. Korean drama may have a strong and attractive impact on the Algerian audience in general and Algerian female viewers in general. Algerian women enjoy watching Korean drama serially and individually, and express their opinions and experiences through social media. These habits reflect their desire for attention to detail and sympathy with the characters and stories, in addition to their desire to communicate with the community that shares in watching Korean drama. Algerian female viewers watch Korean dramas via the Netflix platform because of the high-quality acting and their desire to learn the Korean language, and the main motive is the widespread spread of Malay culture over the following years. All of these reasons and motives indicate the diversity of female viewers’ interests and their enjoyment of watching Korean dramas for the purpose of entertainment and entertainment. -There is a difference in opinions about the aspects of Korean culture that the Netflix platform adopts, as there may be negative views that focus on monopoly, and positive ones that focus on introducing South Korean culture and encouraging cultural exchange. There is a real impact of the Netflix platform on Algerian culture and its impact on Algerian female viewers. This impact reflects their adoption of some aspects of Korean culture and their acceptance in their daily lives. However, this impact is not completely reflected in Algerian culture, but rather is limited to certain aspects such as art, beauty, fashion, food, and language learning. The Neflix platform invests $2.5 billion in producing Korean content and presenting it with the finest technologies, but it deliberately introduces some content that allows Arabs to deny income to Algerian and Arab society in general. key words : Korean drama, Netflix platform, Algerian culture